Effects of Foliar Application of Selenium and Combination with Zinc on Selenium Content in Edible Parts of Lettuce Grown in Mineral Soil - Nayan, Dayang Safinah; Fouzi, Suhaila; Baharuddin, Nurul Husna; Mohd, Ismail (AGRIVITA Journal of Agricultural Science, 2026)
Selenium (Se) is crucial to human health, especially in the immune system and natural defense mechanisms. However, selenium levels in soils are generally low and vary with parent material. Soil deterioration and intensive agricultural activities are among the main factors that contribute to selenium depletion in the soil. Consequently, there is a need to cultivate enriched crops. This study examined the effects of different forms of selenium on plant uptake when used as a foliar spray. Lettuce plants did not show significant differences in weight, height, or leaf number when exposed to different selenium types. However, plants that received the highest level of selenium had fewer leaves but accumulated the highest levels. A further study was conducted in a glasshouse to examine the impact of applying Se, Zn, and a combination of both as foliar fertilizers on the dry matter, crop growth, and uptake by lettuce grown in mineral soil. Results showed that applying selenium and zinc to lettuce leaves improved the content of both minerals compared to the control. No negative effects on growth or yield occurred despite the plants receiving high concentrations of selenium and zinc as foliar fertilizer.